Regional culture: The role of the invisible hand in shaping local family firms’ top management team - Yu, Xiaodong; Zhang, Yuyin; Cheng, Xirong; Li, Huan; Chen, Yujie; Zhou, Weizhong (Frontiers in Psychology, 2022)
Research on family businesses has been focused mainly on the differences between family and nonfamily firms regarding the top management team. This paper explores the differences within family firms under various regional cultures from the perspective of family involvement and family executive compensation. The sample comprised all 625 family firms listed on the Small & Medium Enterprise Board and Growth Enterprise Board of the China Shenzhen Stock Exchange. This study adopted regression analysis to test its hypotheses. Under the influence of strong clan culture, given the high status and profound influence of family in social life, people are accustomed to performing family-based activities. In regions of strong clan culture, family members are more willing to involve in a family business and accept lower economic reward. Particularly, when the financial risk is high, the motivation of maintaining family interests is strong and the effect of regional clan culture is more prominent. Thus, regional culture affects the characteristics of top management team in family firms. This study explains the heterogeneity of family firms’ decision-making from a culture-based perspective and extends existing research on family business from the level of “family firm vs. nonfamily firm” to that of “family firms in different regional cultures”.